Sobre O tronco, romance de Bernardo Élis - Marchezan, Luiz Gonzaga [UNESP]; Souza, Eunice Prudenciano de (My University, 2014)
The conception of O tronco was influenced by Hegel´s ideas. The genesis of this novel is in Bernardo Élis’ purpose of writing a monograph on land ownership conflicts in Goiás, later transformed into a new project, the novel O tronco. The same ideological position of the author gives the argumentative direction of the novel; his ideological background determines the choice of the theme, associated with images expanded by the procedures of argumentation that permeate the literary discourse. Thus, in face of the undeniable aesthetic value of Élis´work, we analyzed O tronco, specifically the argumentation that guides the literary narrative, enhanced by the artistic treatment of violence, its theme, as the result of the struggle for power. The novel was published in 1956; the author, heir to the literary regionalism of the 30s, through an artistic and calculated combination of the story of a local government and literature, accuses, judges the exacerbated domination of a particular social group in a region in Goiás.

A concepção de O tronco tem a influência das ideias de Hegel. A gênese desse romance está no primeiro propósito que teve Bernardo Élis em realizar uma monografia sobre os conflitos de posse de terra em Goiás, posteriormente modificado diante de novo projeto, o do romance O tronco. A posição ideológica do autor dá a direção argumentativa do romance; sua formação ideológica determina a escolha do tema romanesco, partilhado com figuras expandidas pelos procedimentos de argumentação que perpassam o discurso literário. Assim, diante do inegável valor estético da obra de Élis, analisamos, de maneira abrangente O tronco, especificamente, a argumentação que orienta a narrativa literária, realçada pelo tratamento artístico dado à violência, o seu tema, resultante da luta pelo poder. O romance foi editado em 1956; o autor, herdeiro do regionalismo literário da década de 30, por meio de uma combinação artística, bem calculada, entre a história de um poder local e a literatura, acusa, julga o domínio exacerbado de um determinado grupo social numa região goiana.
Keywords: Brazilian Literature; Regionalism; Argument; Literary narrative; Literatura brasileira; Regionalismo; Argumentação; Narrativa literária